The Effectiveness of Traditional Chinese Yijinjing Qigong Exercise for the Patients With Knee Osteoarthritis on the Pain, Dysfunction, and Mood Disorder: A Pilot Randomized Controlled Trial - Zhang, Shuaipan; Guo, Guangxin; Li, Xing; Yao, Fei; Wu, Zhiwei; Zhu, Qingguang; Fang, Min (Frontiers in Medicine, 2022)
Background: Although traditional Chinese Yijinjing Qigong Exercise (YJJQE) is popularly used in China, to alleviate symptoms of people with knee osteoarthritis (KOA), no randomized controlled trials (RCTs) are available to evaluate the effects of YJJQE in patients with KOA. The purpose of this trial is to assess the clinical efficacy of YJJQE for patients with KOA. Methods: A total of 50 participants clinically diagnosed with KOA are randomly (1:1) assigned to the YJJQE group (n = 25) and to the stretching training exercise (STE) group (n = 25), for a 40-min exercise session twice a week for 12 weeks. All outcome measures are collected at baseline and at 12-week ending intervention, which includes the primary outcomes of Western Ontario and McMaster Universities Osteoarthritis Index Scale (WOMAC), the secondary outcomes of visual analog scale (VAS), mental component summary (MCS), physical component summary (PCS), Beck depression inventory (BDI), perceived stress scale (PSS), Berg balance scale (BBS), and the Gait functional mobility data. Results: The YJJQE group did not have any significant changes compared to the control group on the WOMAC score after the 12-week intervention (P > 0.05), though the YJJQE group demonstrated better performance in MCS, BDI, and PSS (P = 0.002, P = 0.001, and P = 0.026, respectively) than the control group. No serious adverse events occurred in either group, and only mild muscle soreness was reported during both exercise treatments. Conclusion: Because no difference between both groups was shown, with regards to the primary outcome measurement (WOMAC), it can hardly explain that the YJJQE had an advantageous effect on patients experiencing the pain and dysfunction of knee osteoarthritis. However, compared to the control group, YJJQE appeared to be associated with improvements in psychological well-being including reduced stress, anxiety, depression, and mood disturbance to manage KOA. Further trials with larger sample sizes and follow-up studies will be required. Clinical Trial Registration:https://www.chictr.org.cn/edit.aspx?pid=60357&htm=4, ChiCTR2000037256.